Morphological Diversity of Amorphophallus gigas (Araceae) in North Sumatra, Indonesia - Rambey, Ridahati; Hakim, Luthfi; Augustina, Sarah; Rahmawaty; Rauf, Abdul; Yuzammi; Suratman, Mohd Nazip (Phytotaxa, 2026)
Amorphophallus gigas is an endemic species in Sumatra with significant ecological and economic value; however, information regarding its morphological variation remains limited. This study aimed to analyze the morphological diversity of A. gigas in several locations in North Sumatra as a basis for conservation strategies. Observations were conducted on 20 individuals per location, focusing on vegetative and generative characters, and analyzed using the UPGMA clustering method with NTSYS software. The results showed that A. gigas populations were divided into two major groups: the South Labuhanbatu, North Padang Lawas, Mandailing Natal group and the North–South Tapanuli Group. The main differences were found in floral organs, particularly the color of the appendix, spathe, and staminate flowers. Cluster analysis produced a similarity coefficient of 0.33, indicating high morphological diversity among populations. This variation reflects the influence of environmental factors on morphological expression and highlights the importance of maintaining distinct populations to support genetic conservation. These findings emphasize that morphological studies can serve as an essential foundation for sustainable management and conservation of A. gigas in North Sumatra.